Educational delays among children living with perinatally-acquired HIV in Johannesburg, South Africa. Issue 4 (2nd April 2020) - Shiau, Stephanie; Arpadi, Stephen M.; Burke, Megan; Liberty, Afaaf; Thurman, Cara; Patel, Faeezah; Strehlau, Renate; Abrams, Elaine J.; Coovadia, Ashraf; Violari, Avy; Kuhn, Louise
ABSTRACT: Little is known about how growing up with HIV impacts educational outcomes in sub-Saharan African children. We evaluated if South African children living with HIV (CLWH) were in the appropriate school grade-for-age compared to uninfected control children. We observed higher rates of not being in the correct grade-for-age in CLWH compared with controls (OR 3.32, 95% CI: 2.07-5.34), adjusted for study site, sex, whether the child's biological father was alive, and caregiver education. Initiation of ART before 6 months of age reduced but did not eliminate this association. Whether these associations are due to biological factors or other social and environmental determinants, and how best to support CLWH to achieve educational goals, warrants further investigation.